Effect of Ethanolic Leaves Extract of Peperomia pellucida (L) Kunth as Antimalarial and Antioxidant - Nanang Yunarto; Hanief Mulia Ar Rossyid; Lisa Andriani Lienggonegoro (Media Penelitian dan Pengembangan Kesehatan, 2018)
In malaria infection, the Plasmodium parasites break down hemoglobin in the host's red blood cells into toxic free heme and amino acids. Plasmodium is also capable of converting free heme to non-toxic hemozoin through a polymerization process. Malaria infection, on the other hand, also triggers the formation of free radicals that affect the pathophysiology of malaria. Suruhan leaf (Peperomia pellucida (L.)Kunth) has long been used as an antimalarial and is known to contain large flavonoids that function as antioxidants. In this study, leaf extraction, inhibitory activity of heme polymerization assay, and antioxidant activity assay were performed. Organoleptically, leaf extract obtained in the form of dry blackish green coloured extractswith a bitter taste and the typical scent of suruhan leaves. The yield of the extract obtained was 18.28%, water content was 7.73%, drying shrinkage was 9.16%, and total ash content was 0.46%. The IC50 value of inhibition activity of heme polymerization of ethanol extract of the Suruhan leaves was 0.93 mg / mL, smaller compared to chloroquine(1.48 mg / mL)while the value of IC50. antioxidant activity of ethanol extract of leaf syrup was 32.94 mg / mL compared to Vitamin C of 4 mg/mL. In conclusion,ethanolic leaves extract of suruhan has inhibitory activity of heme polymerization and antioxidant activity so that it has potentiality as antimalarial drugs